ANALISIS TABUNGAN DALAM PERBANKAN: PENGELOLAAN, PROSEDUR AKUNTANSI, DAN MEKANISME OPERASIONAL REKENING NASABAH - Jessica Anastacia Dame Purba; John Peter Naibaho; Putri Yola Lumbantoruan; Wendy Teguh Putri Zega; Hamonangan Siallagan (Jurnal Akuntansi Kompetif, 2026)
This study aims to comprehensively analyze the savings management mechanism in banking, including the process of account opening, deposits, withdrawals, interest calculations, account closures, and savings gift giving. Savings are one of the most important sources of Third Party Funds (TPF) for banks because they support liquidity and operational stability. This study uses a descriptive qualitative approach through a literature review of banking literature, Financial Services Authority regulations, Bank Indonesia regulations, and supporting documents from the banking industry. The results show that savings management is a series of structured and interrelated processes, where the application of prudential banking principles, accurate accounting records, and transparency to customers are key factors in the success of this product. Savings interest calculations using the simple interest method, recording savings as a bank liability, and account closure mechanisms that comply with regulations have proven to play a crucial role in maintaining the accuracy of financial reports and transaction security. Furthermore, savings rewards were found to be an effective marketing strategy for increasing customer loyalty and interest. This study concluded that good savings management requires integration between operational, accounting, security, and business strategy aspects to maintain public trust and the sustainability of the banking system.